Alat Monitoring dan Notifikasi Penggunaan Daya Listrik Rumah Tangga Berbasis Internet Of Things Menggunakan Blynk 2.0 - Arif Sandira; Jufrizel; Putut Son Maria; Aulia Ullah (Politeknik Caltex Riau, 2022)
Every year the number of electricity consumers continues to increase, but knowledge about electricity is still poorly understood, especially for consumers in the household aspect even though digital kWh meters have been applied, this causes the use of electrical energy to be less efficient. This study aims to create a monitoring tool for the use of electric power as well as a notification so that consumers can save electricity costs. The method used is research and development to improve existing products by testing their effectiveness. This tool uses the PZEM-004T module as a current and voltage reader sensor, and Blynk 2.0 as an internet of things platform. The test results show the tool can read the voltage with a difference of 0.7V and the current with a difference of 0.1433A. The tool can monitor electricity, and there are notifications on tools and smartphones in the form of warnings for 500 Watt usage, increasing the number of usages of Rp. 5000, and Offline conditions. The experiment of implementing the tool for 6 days, consumers were able to save electricity usage as much as 0.51kWh or equivalent to Rp.781.01 compared to without the tool.